Interconnection between Capital Market Indices and Economic Growth: Nigeria’s Perspective (1989-2015) - Afolabi, Babatunde; Awoyemi, Bosede Olanike; Ibimilua, Samuel Taiwo (Advances in Social Sciences Research Journal, 2017)
The study investigates the interconnection between capital market indices and economic growth in Nigeria between 1989 and 2015. In spite of the popular credence that capital market enhances investments-captivating environment, the Nigeria’s capital market appears not to have achieved the anticipated prospect in terms of its (capital market) influence on economic growth. The research employed time series data. The Multiple Regression technique was harnessed to examine the long-run relationship between economic growth and capital market indices such as market capitalization, value of transactions, all shares index, capital flows and stock turnover ratio in the country. The findings show that while market capitalization, capital flow and stock turnover ratio indicate positive and significant influence on economic growth, the all share index, and value of transactions exhibit negative effects on the economic growth in the country. In addition, the degree of responsiveness of economic growth to market capitalization and all shares index is 25.8% and 23.4% respectively. The study revealed 93% total variations in economic growth was accounted for by the predictors. Similarly, it was discovered that market capitalization and the value of transactions granger cause economic growth in the short run. Hence, the study recommends that government should place greater stress on Nigeria’s capital market with a view to refurbishing the cardinal market indices that culminate in long term negativity so as to attain the market enhancement, capital accumulation improvement and national productivity upsurge in the Nigerian economy.